PETROLOGY AND GEOLOGICAL STRUCTURE STUDY OF DARAJAT GARUT GEOTHERMAL AREA - Oktarian Iskandar (Sean Institute, 2023)
This study aims to conduct a petrological study and analyze the geological structure in the Darajat Geothermal Area, Garut. This area is known as a region rich in geothermal resources and has the potential to be developed as a renewable energy source. The research method involves collecting field data, petrological observations, analysis of geological structures, as well as interpretation and analysis of data from various secondary sources. Field data collection includes geological measurements, rock sampling, and mapping of the main geological structures. The results showed that the Darajat geothermal area consists of various rock formations, both pre-caldera and post-caldera consisting of rock types such as basalt, pyroclastic andesite, and andesite lava. There are also minerals such as plagioclase, hornblenda, clinopyroxene, quartz and clay in the rock composition of this area. This study shows that there is a general direction of geological structure from northeast to southwest. There is a system of circular faults and depressions that control the geological characteristics of this area.